Diversity and distribution of dermatophytes and other keratinophilic fungi in the soil of gharana wetland, india - an important stop over site for migratory birds. - SHIFALI SHARMA,; GEETA SUMBALI, (International Journal of Pharma and Bio Sciences, 2017)
The present research work was undertaken to study the diversity of keratinophilic fungi from the unexplored soil of Gharana wetland (J&K), which is situated about 15 km east of the Indo-Pakistan International border in R.S Pura tehsil and is an important wintering and stopover site for migratory birds . The work was done with a view to evaluate the relationship between the keratinophilic fungi and the keratinous material present in the soil as this group of fungi can pose high risk of human and animal mycoses and the migratory birds may even be responsible for their international dispersal. A total of 52 keratinophilic fungal species were recovered which included both dermatophytes and non- dermatophytes. They belonged to 21 genera (Acremonium, Alternaria, Aspergillus, Chrysosporium, Cladosporium, Cunninghamella, Curvularia, Fusarium, Histoplasma, Humicola, Lictheimia, Microsporum, Mucor, Paecilomyces, Purpureocillium, Penicillium, Rhizoctonia, Rhizopus, Sarocladium, Sepedonium and Syncephalastrum) and were recovered by keratin bait technique from the soil of Gharana wetland. Out of these, Aspergillus was represented by maximum of 9 species, which accounts for 17.3% of the total recovered mycodiversity followed in decreasing order by 7 species of Chrysosporium, which contributed 13.46% of the total mycodiversity.The dermatophytes were the highest producers of keratinase, whereas among the non- dermatophytes, Chrysosporium species showed the maximum activity. In view of these observations, it can be safely concluded that most of the keratinophiles recovered from this wetland have the potential of causing mycosis.